PSE meat formation in broiler chickens: a pre-slaughter management case (2018)
The pre-slaughter period in the broiler industry is characterized by very critical stages for the welfare of the animal: the catching, the placement in transport boxes, transportation itself, the wait time at the processing plant before unloading, and unloading prior to hanging the birds. When the appropriate care is not taken to ensure the thermal comfort and well-being of these animals, it can result in great production losses due to mortality or negative alterations in the quality of the meat. A problem that develops, mainly caused by thermal stress, both by the cold or heat, is the formation of PSE (Pale, Soft and Exudative) meat. The main problem with the appearance of this phenomenon is that the sensorial properties of the meat are altered and, therefore, it is rejected by the consumers and the processing plants end up having problems to process it, having to be discarded thus generating huge losses in the industry.